Towards a Whole Spectrum Medicinal Cannabis Extract: Development of a Green Extraction Method - Pourseyed Lazarjani, Seyedeh Masoumeh (Mercedeh) (Auckland University of Technology, 2024)
Introduction: Medicinal cannabis, a subject of increasing research and clinical interest, holds significant potential for addressing a wide range of medical conditions, with its therapeutic applications continuing to expand and evolve. Aims: The aims of this thesis are to develop and validate quantification methods for cannabinoids and terpenes, optimising common extraction methods such as maceration and ultrasound-assisted extraction (UAE), as well as pre- and post-extraction techniques including liquid nitrogen-assisted grinding, dried plant dimensions, and filtration techniques. Additionally, the main objective of this thesis is to develop a green extraction method to capture a whole spectrum of medicinal cannabis extract. Spanning across six chapters, each delving into distinct facets of cannabis extraction and analysis. Methods: Chapter one provides a comprehensive overview of the cannabis plant and its therapeutic effects, quantification methods for cannabinoids and terpenes, various cannabis extraction techniques, and pre- and post-extraction techniques. Drawing insights from previous studies based on the literature, this chapter lays the groundwork for the subsequent chapters. The second chapter focuses on the development and validation of cannabinoids and terpenes quantification methods using HPLC and GC-MS. The optimised ultrasound-assisted extraction method utilises ethanol and hexane as solvents, followed by centrifugation and syringe filtration. Validation of the HPLC and GC-MS methods includes assessing linearity, limit of detection (LOD), limit of quantification (LOQ), recovery, precision (inter-day and intra-day), accuracy (inter-day and intra-day), and matrix effect for 12 cannabinoids and 30 terpenes using appropriate standards. Chapter three highlights the superiority of dynamic maceration over static maceration, emphasising the significant impact of dried plant dimensions/grinding time on the efficiency of cannabinoid and terpene extraction. Chapter four focuses on optimising UAE conditions using response surface methodology, as well as evaluating the influence of liquid nitrogen-assisted grinding and filtration methods on the concentrations of cannabinoids and terpenes within cannabis extracts. The highlight of this thesis is chapter five, which introduces a novel water-based green extraction method utilising oil-in-water emulsions as the extraction solvent. The extract is then separated into water and oil phases for cannabinoid and terpene quantification using HPLC and GC-SPME. Results and conclusion: The results showed HPLC had strong linearity (correlation near 1), low LOD/LOQ values, and 70-120% cannabinoid recovery. GC-MS also exhibited good linearity, with terpene recovery between 80-90% and high sensitivity. Both methods had precision under 10%. Optimisation of Ultrasound-Assisted Extraction (UAE) identified 80W sonicator power as ideal. Liquid nitrogen grinding showed no significant impact but reduced acidic cannabinoids with nonpolar solvents. Syringe filtration doubled cannabinoid concentrations compared to vacuum filtration. A 90:10:5 emulsion in UAE yielded the highest cannabinoid and terpene levels, with additional tests confirming high polyphenol, flavonoid, and antioxidant content.
Keywords: Medicinal cannabis; cannabinoids; terpenes; polyphenols; flavonoids; antioxidant activity; grinding; liquid nitrogen; filtration; extraction; quantification; HPLC; GC-MS; water-based extraction; green extraction; maceration; ultrasound assisted extraction